Evaluation of saturation and erosion of compacted bentonite using electrical resistivity measurement: A numerical study - Hong, Chang-Ho; Kim, Tae-Young; Kim, Jin-Seop; Chong, Song-Hun (Nuclear engineering and technology, 2025)
The hydraulic properties of compacted bentonite are critical for the performance of high-level radioactive waste disposal systems. Conventional methods for monitoring saturation, such as wave velocity, and relative humidity sensors, are often limited by accuracy and practicality in field applications. This study evaluates the effects of saturation and erosion on the electrical resistance of compacted bentonite using a finite element method-based numerical model. A validated electrical resistance module is developed using a generalized mesh modeling technique and applied to simulate variations in resistance under different saturation thicknesses, erosion volumes, and electrode placements. The results show that resistance increases with larger electrode spacing and proximity to the eroded layer but decreases with thicker saturation or closer proximity to the saturated layer. The presence of a copper canister significantly affects resistance measurements, highlighting the need for optimized electrode placement (20–50 mm from the canister) or the use of multiple electrodes. These findings provide a foundation for the practical application of electrical resistivity surveys in field conditions, supporting more effective monitoring of bentonite saturation and erosion processes.